Razbojniški valovi - Tobias, David (Matrika, 2022)
Waves that suddenly emerge on the surface and are unusually high compared to the surrounding waves are referred to as rogue waves. The first part of the article focuses on the history of rogue waves research and physical mechanisms that could explain their formation. The second part provides a detailed explanation how rogue waves can be formed due to constructive interference, which is a consequence of dispersion.
Keywords: dinamika tekočin; fluid dynamics; razbojniški valovi; rogue waves; surface waves; valovanje na vodni gladini